Tissue oxygen availability in children and adolescents with type 1 diabetes mellitus: risk factors for tissue hypoxia. - Pankowska E; Szypowska A; Staniszewska K (Experimental & Clinical Diabetology / Diabetologia Doswiadczalna i Kliniczna, 2007)
Background. Hypoxia is one of the factors affecting the development of diabetic neuropathy and retinopathy. The parameters evaluating tissue oxygen availability, such as oxygen saturation and partial pressure of oxygen, are imperfect and do not provide complete information about the body's oxygen status. Tissue oxygen availability can be evaluated non-invasively using the oxygen status algorithm by Siggaard-Andersen and the new oxygen parameters: oxygen extraction tension (px), concentration of extractable oxygen (cx) and oxygen compensation factor (Qx). To evaluate tissue hypoxia in children with type 1 diabetes mellitus.Material and methods. A total of 42 patients were included in the study. Their mean age was 17.11 years (SD 2.6 years), the mean duration of disease was 6.6 years (SD 3.37 years), the mean HbA[1]c level was 9.34% (SD 2.41%). Patients with acute complications of diabetes were excluded from the study. The following parameters of arterial blood were evaluated and entered into the Oxygen Status Algorithm software developed by Siggaard-Andersen: pO[2], sO[2], pCO[2], pH, TotHb, FCOHb and FMetHb.Results. The results were presented as standardised values (SD) calculated in relation to the normal values contained in the programme. A reduction of px and cx below 1 SD was observed in 16.6% of the patients. The px values significantly correlated with 2,3-DPG (r = 0.89, P < 0.05), total Hb concentration (r = 0.40, P < 0.05) and saturation (r = 0.80, P < 0.05).Conclusions. (1) Children with type 1 diabetes mellitus may develop hypoxia. (2) Significant risk factors for hypoxia include low concentrations of 2,3-DPG, total haemoglobin and saturation. (3) The Oxygen Status Algorithm may be useful in detecting tissue hypoxia in diabetic children and determining risk factors.